Molecular biology of colorectal cancer - Szenajch, Jolanta; Synowiec, Agnieszka; Szarlej-Wcisło, Katarzyna; Cieślak, Agata; Korniluk, Jan; Bodnar, Lubomir (Contemporary Oncology/Współczesna Onkologia, 2006)
A human population affected by colorectal cancer embraces residents of the West or others but with their style of life accepted. The global morbidity and mortality represent 875 K new cases and 570 K deaths per annum, respectively. Colorectal cancer therapy is divided into two main parts, ie. adjuvant chemotherapy and palliative counterpart. For ages the treatment of colorectal cancer has been based upon 5-fluorouracil and leucovorin. Therefore, there is a great need for new drugs to be used effectively in fighting the malignancy. Molecular investigations have shown the particular genes to have influence on development and progression of colorectal cancer, and the huge part of the cases is sporadic. Although, there have been known genetic syndromes in which colorectal cancer is a well-defined part each of them. Identification of genes that have a crucial impact on carcinogenesis, and progression of cancer would be of a great clinical interest. DNA microarray is a molecular technology which has a seminal role on studying biology of human cancers, better molecular level diagnostics, and creativity of novel drugs. This technology offers analysis of thousands of genes or oligonucleotides at the same time during one experiment. Glass slides with printed sequences are made automatically, and are available commercially, as well. The whole processing is also highly automated. High-throughput genetic analysis can detect genes that would be of clinical interest as prognostic or predictive factors. Such factors would be the same considered as a good target to new drugs which could be synthesized according to rules of combinatorial chemistry. The latter technology offers thousands of chemicals to appear within days with potential usage as new targeted drugs.